FRONT OFFICE DEPARTMENT DALAM OPERASIONAL DI SEJAHTERA FAMILY HOTEL DAN APARTMENT - , PARYONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
At this moment Indonesia tourism in the State has experienced rapid growth. This is evidenced by the growing number of accommodation, catering / restaurant, transport / freight services, foreign currency exchange, travel ataraksi, souvenirs and travel agencies. In line with these developments, the hospitality industry needs to get attention as a business entity engaged in accommodation services. The hospitality industry will continue to evolve in line with efforts to improve the quality of service that the hotel operations run smoothly. The purpose of this thesis is to investigate the activities of the Front Office at Sejahtera Family Hotel and Apartment. Data collection methods used in this report are interviews, observation, and literature. The procedure for generating a data report with data that is descriptive of the results described job training in the form of a sentence. From the results it can be seen that the job training Sejahtera Family Hotel and Apartment especially the Front Office Department has a very important role in the operational process of the hotel. All guests staying in activity Sejahtera Family Hotel and Apartment starts handling by the front or the Front Office from guests arrive, stay until the guests leave the hotel. Can be concluded that the major effect in the Front Office operations and become a benchmark Sejahtera Family Hotel and Apartment deserves to be one of the \"three-star hotel\" that can compete with hotels in Yogyakarta.